ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA/I UNIVERSITAS SULTAN AGENG TIRTAYASA JURUSAN EKONOMI SYARIAH 2023 UNTUK BERDONASI DARI SISA PENGEMBALIAN UANG BELANJA DI MINIMARKET - Virki, Aulia Zahirah; Awaliyah, Dillah; Nurfaiza, Ratu Fathia; Fazzari, Tajul; Mukti, Titania (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2023)
This study was conducted to determine the effect of attitudes and behavior of Sultan Ageng Tirtayasa University students class of 2023 majoring in Sharia Economics on the decision to donate from the remaining shopping change at Minimarket. Quantitative research using multiple linear regression analysis methods. The method used for data collection is the questionnaire method as a tool for collecting primary data. The results stated that there was a positive influence between religiosity on student donation interest with a significance value of 0.000 <0.05 and a calculated T value of 3.693> T table value of 1.995. There is no effect of demographic characteristics on student donation interest with a significance value of 0.504> 0.05 and a T value of -0.671 < T table value 1.995. There is no effect of education on student donation interest with a significance value of 0.512> 0.05 and a calculated T value of 0.660 < T table value 1.995. The results also show that there is a positive and significant effect of religiosity, demographic characteristics, and education simultaneously on student donation interest with a significance value of 0.000 <0.05.